2019
DOI: 10.1167/iovs.17-23506
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Change and Incidence of Myopia Among A Group of Highly Selected Senior High School Students in China: A Prospective Study in An Aviation Cadet Prerecruitment Class

Abstract: Refractive change and incidence of myopia among a group of highly selected senior high school students in China: a prospective study in an aviation cadet prerecruitment class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 53 publications
5
23
0
2
Order By: Relevance
“…Previous studies on the behavioural characteristics of juvenile myopia have mainly focused on time spent in outdoor activities, distance and time of near work, sleep, and other possible factors such as light exposure time and electronic product usage. The result that increased outdoor exercise time was a protective factor of myopia is consistent with many studies [ 10 , 21 , 23 25 ]. Having at least 60 minutes of daily exercise [ 23 ] or one additional hour of outdoor time per week [ 26 ] could reduce the odds of a child having myopia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies on the behavioural characteristics of juvenile myopia have mainly focused on time spent in outdoor activities, distance and time of near work, sleep, and other possible factors such as light exposure time and electronic product usage. The result that increased outdoor exercise time was a protective factor of myopia is consistent with many studies [ 10 , 21 , 23 25 ]. Having at least 60 minutes of daily exercise [ 23 ] or one additional hour of outdoor time per week [ 26 ] could reduce the odds of a child having myopia.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, female gender, higher grade, and parental myopia were associated with an increased risk of myopia in children [17,18]. In addition, other studies indicated that parental myopia was one of the risk factors for adolescents' myopia [19][20][21][22]. Regarding the demographic characteristics of our sample, in the myopia group, older age and parental myopia were risk factors for myopia, while male gender was a protective factor against myopia.…”
Section: Discussionsupporting
confidence: 52%
“…Parental myopia, age at the start of primary school, and weekly sleep duration were not associated with the onset of myopia. The results of the present study were similar to those of another study by our research team [19]. In that study, Yao et al found that more hyperopic baseline refraction was a protective factor for incident myopia, and less outdoor activity time and more near work time were risk factors for not only incident myopia but also refractive change.…”
Section: Discussionsupporting
confidence: 91%
“…Another recent longitudinal study in aviation cadets in China included 800 non‐myopic males (mean age 15 years) and found similar results (Yao et al. 2019). A comprehensive ocular examination and detailed questionnaire were given at baseline and each of two follow‐up visits.…”
Section: Recent Findingssupporting
confidence: 57%